Changes in body composition after endurance training and triathlon competition - Puggina, E. F.; Lopes Machado, D. R.; Borges, G. A.; Barbanti, V. J. (Human Movement, 2011)
The aim of this study was to investigate the effects of training and triathlon competition on anthropometry, plasmatic free fatty acids (FFA) and hydration status. Methods. Twelve male triathletes were submitted to a 12-week training program to compete in the "32° Pirassununga Half Ironman". Anthropometric measurements such as skinfold thickness and bioelectrical impedance (BIA) as well as urine and blood samples were collected at three intervals: at the beginning of the training program (M-1), before (M-2) and after competition (M-3). FFA were analyzed using a NEFA-C kit. Urine pH and density was determined using reagent tapes and a manual refractometer. Data were analyzed using one-way ANOVA and the Tukey-Kramer post-test (p < 0.05). Results. No differences were found for body mass (M-1 = 71.83, M-2 = 74.22, M-3 = 72.15 kg), percent body fat using skinfolds (M-1 = 10.98, M-2 = 10.92, M-3 = 10.40%), urine density (M-1 = 1.02, M-2 = 1.01, M-3 = 1.02) and urine pH (M-1 = 6.00, M-2 = 5.92, M-3 = 5.35). For BIA and FFA, differences were found after competition (BIA: M-1 = 13.54, M-2 = 13.91, M-3 = 9.45%; FFA: M-1 = 0.16, M-2 = 0.15, M-3 = 1.69 mEq/L). Conclusions. These results illustrate the effects of training and competition on body composition and FFA mobilization. Additionally, after five hours of effort, no evidence of dehydration was found after the race.